Acute Onset Common Peroneal Nerve Palsy Secondary to Fibular Head Osteochondroma in an Adolescent: A Case Report - Kevin Jain; Sandeep Patil; Stavan Amin; K S Akshay; Sanjeev Ghildiyal (Journal of Orthopaedic Case Reports)
Introduction: Common peroneal nerve (CPN) palsy in the pediatric population is rare, particularly in the absence of trauma. Among the uncommon causes, osteochondroma of the fibular head can lead to compressive neuropathy. Early diagnosis and prompt surgical intervention are crucial to achieving optimal outcomes. Case Report: A 9-year-old male child with acute onset of foot drop leading to high stepping gait. Clinical examination revealed complete loss of left ankle dorsiflexion with no sensory loss. In comparison to other right knee, there was a smooth rounded prominence felt over the fibular head and neck. Radiological and electromyography investigations suggested sessile bony swelling possibly osteochondroma of fibular head denting on Common peroneal nerve (CPN). Early surgical intervention in the form of osteochondroma excision and neurolysis of the CPN offered complete recovery. We describe the case of a 9-year-old boy who had an osteochondroma of the fibular head resulting in common peroneal neuropathy and full foot drop. We go over the diagnosis, course of treatment, and body of research on nerve issues in paediatric children associated with osteochondroma. Conclusion; Atraumatic common peroneal palsy is rare in adolescent age. Fibular head osteochondroma should always be kept in mind considering age group and possible location of pressure nerve palsy which fully recovers with early surgical intervention.